Vascular Abnormalties in Neurofibromatosis Type 1 - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The spectrum of cerebrovascular abnormalities (CVA), including moyamoya, was evaluated in a retrospective chart review of 353 patients with neurofibromatosis type 1 (NF1) seen at the Children's National Medical Center, Washington, DC, from 1995 to 2003.